Use of Social Resources by Elementary Schools in Taiwan and Resource Acquisition Strategies: Perspectives of Outstanding Principals - Huang, Tzung-Hsien (Journal of Social and Development Sciences, 2013)
Due to rapid social changes and shrinking family size, the management of Taiwan’s elementary schools faces many severe challenges. The question of how to enhance school competitiveness has become an important issue that must be addressed by school principals. Looking from the resource-based view and the organizational ecology perspective, the acquisition of social resources by schools is an important mission for today’s principals. Because of the great importance of social resources to school operation, and the great lack of research on the effective acquisition of social resources, this study seeks to employ systematic methods to examine how outstanding benchmark principals in Taiwan utilize social resources in order to acquire the resources their schools need for sustainable operation. Hence, the main purpose of this study is to explore how schools use social resources in order to maintain their competitiveness, and their strategies for acquiring social resources, from the perspectives of outstanding principals. The results of this study reveal (1) eight findings concerning how public elementary school principals’ perspectives on the use of social resources, such as active interaction with the community, establishment of networks of diverse relationships, obtaining recognition of superior teaching, and school marketing; and (2) ten findings concerning elementary school principals’ strategies for acquiring social resources, such as maintenance of personal relationships, establishment of distinctive school features and enhancement of teaching performance, and skillful use of communication to acquire social resources. These important research results reveal a wide range of social resource utilization and acquisition strategies, and suggest the necessity and value of the implicit knowledge and wisdom that principals bring to bear in the workplace.